Memorial: bastidores da formação profissional de um professor de educação básica - CUNHA, João da (2023)
When we talk about higher education comes to mind the word difficult, at least for us who came from below; I remember that in my city when we saw a doctor passing people commenting ''he graduated in such a place'', ''it's not anyone who can study 05 years to be working today'' this did not happen only with the doctors, they needed to see when a delegate passed. We had the greatest admiration for teachers, who often did not even have higher education, taught only with completed teaching, sometimes not even needed so much. There in our reality, not for a second I imagined myself completing my graduation today, especially by a federal through PARFOR. The challenges were enormous, due to access to the precarious education I had in my childhood; the authorities did what they could to alleviate the high school dropout rate, the lack of teacher training, the precarious structure of the schools, but in fact it was still insufficient. In addition to showing the reality of the difficulty that this trajectory of a humble person behind the scenes of higher education training is, I will also show my current vision of education, a vision that I put into practice in my daily life as an educator. When you finish reading, I hope you understand the importance of offering higher education to needy people, how it transforms realities, brings us the light of society, empowers us to train others like us. Teaching and learning is the only way to guarantee the rights and duties of citizens, it is the only way to guarantee a dignified life for people, it is the only way for us to evolve. Without study, without knowledge, we are walking quickly towards social injustices. There are many challenges in attending PARFOR, among so many challenges I can highlight my journey to get here. I don't come from continuing education, I didn't follow the rites of a common academic, my life trajectory didn't allow that. And now that I've finally made it, not with that energy of academics in their prime, but with the serenity of an adult who has already fought many battles.